Recent Advances on Graphene Quantum Dots for Electrochemical Energy Storage Devices - Zahir, Noura; Magri, Pierre; Luo, Wen; Gaumet, Jean Jacques; Pierrat, Philippe (Energy & environmental materials (Hoboken, N.J.), 2022)
Graphene quantum dots (GQDs) which are nanofragments of graphene with an average size between 2 and 50 nm have attracted much attention due to their outstanding properties such as high conductivity, high surface area, and good solubility in various solvents. GQDs combine the quantum confinement and edges effects and the properties of graphene. Therefore, GQDs offers a broad range of applications in various fields (medicine, energy conversion, and energy storage devices). This review will present the recent research based on the introduction of GQDs in batteries, supercapacitors, and micro‐supercapacitors as electrodes materials or mixed with an active material as an auxiliary agent. Tables, discussed on selected examples, summarize the electrochemical performances and finally, challenges and perspectives are recalled for the subsequent optimization strategy of electrode materials. This review is expected to appeal a broad interest on functional GQDs materials and promote the further development of high‐performance energy storage device. Graphene quantum dots (GQDs) were discovered recently and their fascinating physical and chemical properties make them widely studied on the field energy storage. Prepared either by top‐down or bottom‐up techniques GQDs enhance nearly systematically the properties of batteries and supercapacitors with the increase of the electrical conductivity which help the electron charge transfer.